Circumstantial evidence and qarinah: an overview from the Malaysian legal system / Shahdanizam Saharuddin and Muhammad Afiq Abu Bakar - Saharuddin, Shahdanizam; Muhammad Afiq, Abu Bakar (2011)
Circumstantial evidence and Qarinah is both the smaller branch of evidence system in their respective field which is derived from presumption and surrounding factors to be used in trials and proceedings. Circumstantial evidence is being governed by the established Evidence Act 1950 and Qarinah is inserted into the Syariah courts evidence system according to States and territories, for example the Syariah Court Evidence (Federal Territories) Act 1997. It is undeniable that these two branches of evidence systems are much more important nowadays as cases which have clear and direct evidences are hardly to be found in our court system. The criminals and wrongdoer are getting smarter in concealing their crimes to avoid being Gonvicted of an offence, and parties in disputes are experiencing a harder situation is establishing their claims because of lack of direct evidences. Both system has its own principles and methods in dealing with circumstantial evidence and is currently being used in our judiciary and courts system. However, further studies and monitoring mechanism must be carried out to make sure the workability of these two branches of evidence because it is purely subjective, and the evaluation process is done according to the skills or understandings of legal practitioners. Conversely, each state in Malaysia has their own Syariah evidence system which is being put under the jurisdiction of the State Administration and government. All these enactments are similar in nature and provisions drafted, only the way it is being arranged are different from one another. Thus, this project paper limit itself to refer to Syariah Court Evidence (Federal Territories) Act 1997 for the provisions and laws of Islamic evidence system which will be compared and evaluated with the Evidence Act (1950). Furthermore, only the issues concerning circumstantial evidence and Qarinah will be discussed in this project, such as the definition, sources, nature, principles and application. It will be discussed and compared accordingly for the differences and similarities of each other in order to find possible suggestions and enhancement in the future.